Pemberdayaan Ekonomi Keluarga Melalui Permodalan Nasional Madani Mekaar di Desa Watu Lanur, Manggarai Timur, Nusa Tenggara Timur - Ananda Fikriyah Hasan; Khaerul Umam Noer (Perspektif Administrasi Publik dan hukum, 2025)
Watu Lanur Village is one of the villages in Lamba Leda District, East Manggarai Regency, NTT which belongs to the 3T area (underdeveloped, foremost and outermost), based on Perpres No. 63 of 2020. The village is experiencing low development, geographical location is in the hills, far from urban areas. The village community is still carrying out traditional traditions, one of which is Belis Custom, which causes people to often experience difficulties. PT Permodalan Nasional Madani provides special services for pre -prosperous women through the provision of capital called PNM Mekaar to start a business or who wants to develop a business. The purpose of this study is to determine the success of the capital program in empowering the family's economy in Watu Lanur Village. Data collection of this study from primary data and secondary data, with observation data collection techniques, interviews, and documentation. The method used by this research is descriptive with a qualitative approach. The focus of the problem of this research on families who experience economic difficulties due to traditional traditions. The results of this study indicate that PNM Mekaar is quite successful in providing capital to overcome the sustainability of the main business in the village, namely pigs. Pig -livestock becomes the backbone of the family economy according to tradition there. Every traditional event requires pigs to sacrifice. Obstacles to the capital program in this village, namely the absence of training held by PNM Mekaar caused members not to use capital according to the designation. There is a need for assistance and training to ensure that members can utilize capital productively, so as to improve economic welfare while maintaining tradition.